Effective Average Tax Rates for Permanent Investment - Klemm, Alexander (IMF Working Papers; Working Paper, 2008)
This paper extends the effective average tax rate (EATR) developed in Devereux and Griffith (2003) by relaxing the assumption of a one-period perturbation in the capital stock. Instead it allows a permanent investment. While this may appear a small change, it has important implications. First, it allows the EATR to be calculated in the presence of tax holidays, which are an important part of tax systems, especially in developing countries. Second, it reveals an interesting feature of the original EATR: despite the assumption of a one-period investment, the original measure is informative about long-term investments, thanks to the assumption of pooled depreciation. Without this assumption-which is justifiable in a few countries only- the EATR based on one-period perturbation in the capital stock would be less useful for analyzing medium and long-term investments.